2008
DOI: 10.2105/ajph.2007.116038
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Orphanhood and Children’s Psychosocial Distress: Theoretical Framework Tested With Data From Zimbabwe

Abstract: Nyamukapa et al. | Peer Reviewed | Research and Practice | 133 RESEARCH AND PRACTICE  Objectives. We measured the psychosocial effect of orphanhood in a subSaharan African population and evaluated a new framework for understanding the causes and consequences of psychosocial distress among orphans and other vulnerable children.Methods. The framework was evaluated using data from 5321 children aged 12 to 17 years who were interviewed in a 2004 national survey in Zimbabwe. We constructed a measure of psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
164
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(180 citation statements)
references
References 22 publications
11
164
3
Order By: Relevance
“…HIV testing of older children has not been emphasized because, until recently, long-term survival in the absence of treatment following MTCT was thought to be uncommon. 20 This means that HIV testing for young people in Zimbabwe can only be accessed in health-care facilities, with no freestanding HIV-testing services for children less [21][22][23] We found that most children were diagnosed following presentation with acute illness; only a minority accessed testing through primary care or freestanding HIV-testing services.…”
Section: Discussionmentioning
confidence: 84%
“…HIV testing of older children has not been emphasized because, until recently, long-term survival in the absence of treatment following MTCT was thought to be uncommon. 20 This means that HIV testing for young people in Zimbabwe can only be accessed in health-care facilities, with no freestanding HIV-testing services for children less [21][22][23] We found that most children were diagnosed following presentation with acute illness; only a minority accessed testing through primary care or freestanding HIV-testing services.…”
Section: Discussionmentioning
confidence: 84%
“…Exposure to eight or more adversities increases the risk of negative mental outcomes by 5.7 times (Winslow et al,2005;Nyamukapa et al, 2008;Kumakech et al, 2009). Thus, the results of the empirical investigation indicated that all the children in the research group are at risk for poor developmental outcomes which may compromise their development and future success.…”
Section: Discussionmentioning
confidence: 94%
“…It usually involves a lengthy process of multiple stressors or adversities and changes occurring before, during and after the death. This process may include facing adversities such as parents' illness and death, consequent disintegration of the family structure, poverty, homelessness, relocation, trauma and major adjustments in placement in residential care, stigmatisation, societal discrimination, exploitation and abuse (Richter, 2004, Nyamukapa et al,2008.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a growing body of literature documenting the increased psycho-social vulnerability of such children (Bauman and Germann, 2005;Nyamukupa et al, 2008), although Levine et al (2005) have noted that, in many cases, the apparent 'exploitation' of fostered orphans (being taken out of school to perform farmwork, for example) may be essential for household survival.…”
Section: Fostering and Orphanhood In Malawi And Southern Africa: Histmentioning
confidence: 99%